Analysis of the effect of restricting smartphone use on overcoming student behavior - Aqbar, Khaerul; Azwar, Azwar; Indriani, Dewi; Rifai, Awal; Mutahharah, Mutahharah (Institute of Computer Science (IOCS), 2024)
The use of smartphones in the STIBA Makassar environment has the potential to cause students to tend to behave defiantly, especially in aspects of the Sharia and its practice, and is not in line with what is expected. With concerns about this potential, regulations limiting the use of smartphones have been established as an Islamic social control so that guidance in the STIBA Makassar environment can run as expected and be able to direct students to maintain their behavior in life. This research was conducted with the objectives, namely to analyze the influence of regulations limiting the use of smartphones as Islamic social control on overcoming student behavior at STIBA Makassar. This research uses primary data through questionnaires and a quantitative approach through Descriptive Statistics techniques, and component or variant-based Structural Equation Modelling (SEM) with Partial Least Square (PLS). The results of the research show that the Regulations Restricting the Use of Smartphones as Islamic social control have a positive and significant influence on the Management of Student Behavior, which means that the higher the quality of the implementation of the Regulations Restricting the Use of Smartphones, the higher the quality of the Management of Student Behavior.